Research on the interest of local governments in the use of artificial intelligence in flood risk management in Poland - Wrzalik, Artur (Analiza stopnia zainteresowania samorządów lokalnych wykorzystaniem sztucznej inteligencji w zarządzaniu ryzykiem powodziowym w Polsce, 2021)
The aim of the article was to analyse the degree of interest in the implementation of artificial intelligence methods in the area of crisis management related to flood risk in local government units in Poland. Pilot studies were carried out with the use of a questionnaire and direct telephone interview in 47 selected local governments located in Poland. The respondents assessed the current crisis management system and referred to the possibility of using artificial intelligence solutions in the analysed area. On the basis of the obtained results, it can be concluded that the surveyed entities show significant interest in the proposed solution and have specific expectations towards them. Most of the works devoted to flood risk management in Poland focus on solutions intended for the national level, not local one. The article aimed to highlight the need to fill this research gap.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 3 (61), s. 58-72
Keywords: crisis management; flood risk management; artificial intelligence; zarządzanie kryzysowe; zarządzanie ryzykiem powodziowym; sztuczna inteligencja